In search of first contact : the Vikings of Vinland, the peoples of the dawnland, and the Anglo-American anxiety of discovery - Kolodny, Annette, 1941-2019 (Online access with subscription: Duke University Press., 2012)
A radically new interpretation of two medieval Icelandic tales, known as the Vinland sagas, considering what the they reveal about native peoples, and how they contribute to the debate about whether Leif Eiriksson or Christopher Columbus should be credited as the first ""discoverer"" of America.